Structure and biodiversity of zooplankton communities in freshwater habitats of a Vereda Wetland Region, Minas Gerais, Brazil - Pinese,Olívia Penatti (2015)
Abstract Aims: Vereda wetlands are among the most important aquatic habitats in Brazilian savannah (Cerrado) because of their association with river springs and its relevancy for biodiversity conservation. This study aimed to determine and compare the biodiversity of zooplankton in vereda lakes, differentiated by the presence or absence of aquatic macrophytes at an environmental reserve in Uberlândia, Minas Geais, Southeastern Brazil. Zooplanctonic abundance patterns and their relation with environmental parameters were also discussed and presented through multivariate statistics. Methods Twelve samples were taken at water surface, at 15-day intervals in 2006. It was observed a total richness of 75 species, including 12 genera, 29 species and one sub-species as new records for Minas Gerais State. Results Rotifers were the predominant group and Lecanidae was the most diverse family. Among cladocerans, Chydoridae showed the greatest richness and Bosminidae the highest abundance. Few adult copepods were sampled in this study, but nauplii were very frequent. Cyclopidae was the most common family among copepods and there was no record of Calanoida. Conclusions The difference in composition among the studied lakes was remarkable. The lake with macrophytes showed the greatest richness but the lowest density, and the opposite situation occurred in the other lake. This can be explained by the fact that aquatic macrophytes, as primary producers, exert a bottom-up effect on zooplankton community, sustaining a high local diversity in contrast with a low numeric abundance of these microorganisms. Therefore, this pattern may have been created by the surround heterogeneity and, at the same time, by the reduction of available minerals of the system caused by macrophyte matter fixation. Many studies on zooplankton need to be developed in palm swamp communities in order to better comprehend the biological diversity and the energy balance in different habitats for the conservation of aquatic ecosystems.